Propuesta de mejora del proceso ¿Certificación de Registro Sanitario de Alimentos¿ Inspi-Quito - Velasco Yépez, María Verónica (2014)
The objective of this project is to develop a proposal to improve the process emission of health record for food products registration for the first time in INSPI - QUITO , prioritizing causes found in the diagnosis of the current process and approach possible solutions to them. improvement proposals include: proposal for standardization of methodology review of procedures, proposal planning and distribution of work, communication proposal these proposed will have indicators to assess the continuous process improvement.